2016
DOI: 10.4103/0971-4065.164232
|View full text |Cite
|
Sign up to set email alerts
|

High hemodialysis vascular access flow and impaired right ventricular function in chronic hemodialysis patients

Abstract: There are limited data showing right ventricular preload increase due to high-flow arteriovenous fistulas (AVFs). This cross-sectional study investigated whether high AVF flow had an impact on right ventricular function in patients undergoing hemodialysis. Sixty-four patients aged between 18 and 85 years who were on routine hemodialysis with >2 hemodialysis sessions per week for at least 3 months via an AVF were studied. Patients with inadequate flow fistulas, severe chronic obstructive pulmonary disease, hist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 16 publications
1
4
0
2
Order By: Relevance
“…Momtaz 40 in their study found value to be 28%. However, Yilmaz 41 in their study reported that 34.09% subject…”
Section: Avfs and Right Ventricular Dysfunctionmentioning
confidence: 88%
“…Momtaz 40 in their study found value to be 28%. However, Yilmaz 41 in their study reported that 34.09% subject…”
Section: Avfs and Right Ventricular Dysfunctionmentioning
confidence: 88%
“…Uma proporção significativa de pacientes com etiologia desconhecida foi relatada na literatura, 16,2% dos idosos na Índia12, 5,9% nos EUA, 18% no Reino Unido13 e, da mesma forma, 14,8% no Iran14. Os dados encontrados em Juazeiro foi que 28,3% dos casos eram de etiologia desconhecida e pode refletir a 9 falta de conscientização sobre a doença, a deficiência no diagnóstico precoce e atraso no encaminhamento precoce ao especialista (30,31) e a Nefropatia diabética, como principal causa, contrastou com os dados da SBN, podendo supor uma menor prevenção de complicações renais na localidade. ( 13)…”
Section: Discussionunclassified
“…A força foi avaliada de 0 a 5 pontos, 0 corresponde à ausência de contração; 1 ponto apresenta contração muscular; 2 pontos possui uma contração fraca; 3 pontos caracteriza uma contração regular; 4 pontos boa contração e 5 pontos contração normal. (4) Quanto à variável satisfação, o indivíduo foi convidado a pontuar em uma escala de 0 a 5 pontos, na qual 0 corresponde a insatisfeito e 5 satisfeito[8] A pontuação máxima obtida é de 35 pontos e o score final foi classificado como excelente (34-35 pontos), bom(28)(29)(30)(31)(32)(33), regular(21)(22)(23)(24)(25)(26)(27) ou ruim (0-20).…”
unclassified
“…Immediately after the creation of an AVF, there is an increase in cardiac output (CO) due to the reduction in peripheral resistance, an increase in sympathetic nervous system activity and an increase in stroke volume and heart rate [10]. Many studies showed that the creation of an AVF leads to left ventricular hypertrophy [11] and diastolic dysfunction [5], sometimes leading to left ventricular dilatation and impaired left ventricular and right ventricular systolic function [4,12], which can be the onset of high output heart failure, without linear relation between vascular access flow (Qa) and CO [8]. High output heart failure is defined by symptoms of heart failure (dyspnea, orthopnea, peripheral or pulmonary edema) in the presence of an above-normal cardiac index (CI) (i.e.…”
Section: Introductionmentioning
confidence: 99%